Integração das TDIC na formação de professores em Cingapura: entre intenções, ações e concepções - Pasinato, Nara Maria Bernardes (2017)
This paper focuses on analyzing the intentions and actions of the use of ICT by future teachers in training in Singapore. The main objective is to compare if after ten weeks of compulsory training these future teachers continued with the same intentions of using the technologies or if their intentions had altered. With that intent, a mixed model research was developed with qualitative and quantitative characteristics with a group of 12 future teachers in training at the National Institute of Education in Singapore and 235 students from local schools during the years of 2014 and 2015. The theoretical basis made use of the Unified Theory of Acceptance and Use of Technology from Venkatesh et al. (2003), Maor and Fraser (2005) when using the Constructivist Media Learning Environment Survey, Almeida and Valente (2011, 2012) as references for integrating technologies, Ertmer (1999, 2005) , Richardson (2003) and Teo(2011) as the basis for the study of beliefs and attitude , Jonassen (1999, 2005) and Figueiredo and Afonso (2006) regarding the learning environments and educational context. ISTE (2008), UNESCO (2010), Koehler and Mishra (2008) and Costa et al (2008) were used to describe teachers’ competencies for the use of technology. The results show that there is a decrease in the intended use of technologies by future teachers, which may indicate a lower integration of technologies in the classroom. There is evidence that teachers do not realize how technology can assist the learning process of their students, being a laborious activity with little effect, in their perception. General, teachers did not know how to use technology to create a constructive learning environment in order to actualize the integration of technologies. Inferences show that the teacher training course needs to better develop the classes planning processes, focusing on technology supported learning and thus the future teacher is able to realize the effective integration of ICTs in teaching process and promote a student center learning. At the end a model that combines the elements unveiled during the research is proposed, which are indicated as factors that interfere in the integration of technologies in the school context. Beliefs and Learning Knowledge emerge as indicators that are capable to change the path of teacher training for the use of ICT, being recommended to be developed so that it can effectively carry these processes that were so hardly encouraged and advocated for the education on the 21st century